New Type of Short High‐Frequency VLF Patches ("VLF Birds") Above 4–5 kHz. Issue 4 (30th March 2021) - Manninen, Jyrki; Kleimenova, Natalia; Turunen, Tauno; Nikitenko, Alexander; Gromova, Liudmila; Fedorenko, Yury
Abstract: The new type of daytime natural very low frequency (VLF) whistler mode emissions of the magnetospheric origin was found in the VLF observations at Kannuslehto station ( L ∼ 5.5) in Northern Finland. The events occurred at the frequencies above 4–5 kHz even up to 15 kHz. These emissions have never been observed earlier in the spectrograms because they were hidden by strong impulsive atmospherics (sferics) in the same frequency range originating in lightning discharges. After filtering out the sferics, we surprisingly discovered completely new types of high frequency right‐hand polarized peculiar VLF emissions with various unusual dynamic spectra. These new VLF emissions typically occur as a sequence of a number of short (∼1–3 min) burst‐like structures or single short patches with the total duration up to a few hours. The spectral peculiarities of several long‐lasting VLF events as well as individual short VLF patches are discussed. The dynamic spectra of these new VLF patches raise the question of the temporal and spatial details of the wave‐particle interactions in the magnetospheric plasma. These emissions are observed only under quiet or weakly disturbed space weather conditions, but during small negative values of the Dst index, indicating the presence of a certain excess of the radiation belt electrons. Note, these high frequency VLF patches are observed at the frequencies much higher than the half of the equatorial electron gyrofrequency which is equal to ∼2.7 kHz at L ∼ 5.5. It seems that these emissions are generated deep in the magnetosphere, but the detailed nature, generation region, and propagation behavior of these newly discovered VLF emissions remain unknown. An appearance of high frequency VLF patches could be an indirect indicator of a local enhancement of electron fluxes in the radiation belt that are not directly measured and may occur even in the absence of visible ground‐based geomagnetic disturbances. Further researches may shed new light on wave‐particle interactions occurring in the Earth's radiation belts. Key Points: New and unexpected short patches of natural very low frequency (VLF) emissions above 4 kHz with variable spectral structure Kannuslehto (KAN, L ∼ 5.5) in Finland The discovered VLF patches are observed at the frequencies much higher than the half of the equatorial electron gyrofrequency at L ∼ 5.5 These emissions typically occur as a sequence of short (∼1–3 min) burst‐like structures, and observed under quiet geomagnetic conditions